Congenital Bladder and Urethral Agenesis: Two Case Reports and Management - Salahaddin Delshad; Hadith Rastad; Parham Mardi (Advances in Urology)
Background. Agenesis of the bladder and urethra is a rare congenital anomaly, with a very few living cases reported in the literature so far. Case Presentation. We are reporting two female patients (3 and 6 years old) with bladder and urethral agenesis who presented with urinary incontinence. In both patients, magnetic resonant imaging (MRI) revealed a case of bladder and urethral agenesis with normal ureters draining into the vagina. Patients underwent a neobladder and conduit creation surgery. The neobladder was constructed from the whole cecum and a part of the ascending colon, followed by an anastomose of the ureters into the neobladder in a nonrefluxing fashion; the appendix was used simultaneously as a continent catheterizable conduit. The two patients attained urinary continence postoperatively. Conclusion. We reported two cases of bladder agenesis, and for the first time, we have performed neobladder creation surgery using the cecum and ascending colon. One-year follow-up did not reveal any complications.